2002
DOI: 10.1073/pnas.022581999
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of catastrophic events: Material rupture, earthquakes, turbulence, financial crashes, and human birth

Abstract: We propose that catastrophic events are ''outliers'' with statistically different properties than the rest of the population and result from mechanisms involving amplifying critical cascades. We describe a unifying approach for modeling and predicting these catastrophic events or ''ruptures,'' that is, sudden transitions from a quiescent state to a crisis. Such ruptures involve interactions between structures at many different scales. Applications and the potential for prediction are discussed in relation to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
196
1
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(211 citation statements)
references
References 72 publications
2
196
1
7
Order By: Relevance
“…floods [30], earthquakes [31], snow avalanches [32], to financial crises [33] and social reactions to extreme events [34]. Most of these natural systems have a complex evolution characterized by catastrophic, extreme events that appear at intermittent intervals and have a large impact on the long-term behavior of the systems [35]. In physics, determining the likelihood of these rare events is important to a variety of problems.…”
Section: Quantitiymentioning
confidence: 99%
“…floods [30], earthquakes [31], snow avalanches [32], to financial crises [33] and social reactions to extreme events [34]. Most of these natural systems have a complex evolution characterized by catastrophic, extreme events that appear at intermittent intervals and have a large impact on the long-term behavior of the systems [35]. In physics, determining the likelihood of these rare events is important to a variety of problems.…”
Section: Quantitiymentioning
confidence: 99%
“…Regarding any possible existing earthquake precursors Geller et al (1997) also state "Thousands of observations of allegedly anomalous phenomena (seismological, geodetic, hydrological, geochemical, electromagnetic, animal behavior, and so forth) have been claimed as earthquake precursors, but in general, the phenomena were claimed as precursors after the earthquakes occurred". Furthermore, Sornette (2002) wrote "There is a series of surprizing and Published by Copernicus Publications on behalf of the European Geosciences Union and the American Geophysical Union.…”
Section: Introductionmentioning
confidence: 99%
“…Kossobokov and Keilis-Borok [112] have explored similarities of multiple fracturing on a neutron star and on the Earth, including power-law energy distributions, clustering, and the symptoms of transition to a major rupture. Sornette and Helmstetter [113] have presented occurrence of finite-time singularities in epidemic models of rupture, EQs, and starquakes. Abe and Suzuki [114] have shown that internet shares with EQs common scale-invariant features in its temporal behaviours.…”
Section: Universality Among Various Geophysical and Biological Catastmentioning
confidence: 99%